DNA barcodes and morphology confirm a new species of Rheocricotopus (Psilocricotopus) orientalis group (Diptera: Chironomidae) - Lin, Xiao-Long; Yu, Hai-Jun; Wang, Qian; Bu, Wen-Jun; Wang, Xin-Hua (Zootaxa, 2020)
Morphology and DNA barcodes confirm a new chironomid species within the Rheocricotopus (Psilocricotopus) orientalis group (Diptera: Chironomidae). Rheocricotopus (Psilocricotopus) kongi Lin et Wang sp. n. is described and illustrated based on adult male from Hainan, China. Key to adult males of the R. orientalis group is given.